NILAI-NILAI SEJARAH DALAM NOVEL RASINA KARYA IKSAKA BANU SERTA PEMANFAATANYA SEBAGAI BAHAN AJAR TEKS NOVEL - Rizqi Utami, Wulan Nur; Adham, M. Januar Ibnu; Suntoko, Suntoko (Peneliti.net, 2024)
Historical values in a historical work such as a historical novel are very important to explore as a way to foster a high sense of nationalism. This research aims to describe the structure of intrinsic elements, the form of historical values, and the use of historical values in the novel Rasina by Iksana Banu in novel text teaching materials in high school. The subject of this research is the novel Rasina by Iksaka Banu with the research object being intrinsic elements, forms of hybridity, mimicry and ambivalence as well as historical values in the novel Rasina by Iksaka Banu. The research is qualitative with descriptive methods. The research results show that the intrinsic elements of the Rasina novel consist of theme, plot, characters, point of view, setting, language style and message. There are two forms of mimicry, namely lifestyle mimicry and mimicry in the form of Dutch imitation. Hybridity in the content of Rasina's novel is represented through the use of Dutch by the natives of the Banda Islands. Meanwhile, ambivalence can be seen from the character Kalabaka Maniasa, a native who is fluent in Dutch. The historical value contained is the conquest of the Banda Islands by the Vereenigde Oostindische Compagnie (VOC) in 1621. The results of the analysis of the intrinsic elements and historical values in the Novel Rasina by Iksaka Banu can be used as teaching material in the form of a module for Class XI.